2014
DOI: 10.1353/hpu.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

Religious Beliefs and Cancer Screening Behaviors among Catholic Latinos: Implications for Faith-based Interventions

Abstract: Although most U.S. Latinos identify as Catholic, few studies have focused on the influence of this religious tradition on health beliefs among this population. This study explores the role of Catholic religious teachings, practices, and ministry on cancer screening knowledge, attitudes and behaviors among Latinos. Eight focus groups were conducted with 67 Catholic Latino parishioners in Massachusetts. Qualitative analysis provided evidence of strong reliance on faith, God, and parish leaders for health concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 94 publications
2
39
0
3
Order By: Relevance
“…No research was found to support this result. Previous studies showed religious beliefs promote positive health behaviors or health care utilization [24,25], and patient activation is related to health behaviors or health outcomes [7][8][9][10][11]. So it could be guessed indirectly that religious beliefs may promote positive health behaviors or health care utilization through patient activation.…”
Section: Discussionmentioning
confidence: 99%
“…No research was found to support this result. Previous studies showed religious beliefs promote positive health behaviors or health care utilization [24,25], and patient activation is related to health behaviors or health outcomes [7][8][9][10][11]. So it could be guessed indirectly that religious beliefs may promote positive health behaviors or health care utilization through patient activation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, having direct contact with the pastors often required a high level of call attempts, which were often fielded gby the Church Secretaries. An additional factor that influenced the need for numerous contact attempts is that parish leaders serve a variety of roles in their communities, and therefore, have competing priorities for their time (Allen et al, In press). With this in mind, we conducted recruitment and survey activities at all times of the day and days of the week.…”
Section: Discussionmentioning
confidence: 99%
“…At the start, we formed a Community Advisory Board (CAB) with representatives from faith-based, health, and social service organizations. We also identified contextually appropriate strategies for engaging faith communities by conducting 18 key informant interviews among Latino community leaders and eight focus groups with a total of 67 parishioners (Allen et al, In press). We used this formative research in combination with ongoing input from CAB members to develop and adapt strategies for continuous community and leadership engagement in research activities.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Latinos are also more likely to pray daily in a qualitative study also perceived a connection between spirituality and health, emphasizing that their spiritual beliefs are associated with increased health behaviors such as health care utilization and cancer screenings. 20 Finally, spirituality has been linked to healthy living (ie, stress reduction, avoiding tobacco) as well as an enhanced ability to cope with adverse health outcomes among Latina women. 15,21,22 While the relationship between spirituality and health appears to be robust in the general population, less is known about this relationship among Latinos, and in particular Latino men.…”
Section: Introductionmentioning
confidence: 99%